MODELING THE PROCESS OF FORMING THE COMPETITIVENESS OF LEADERS OF THE PRESCHOOL EDUCATION SYSTEM - Eshqurbonov Anvar Abdiqayimovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article analyzes the model of ensuring the competitiveness of preschool education system leaders. Modeling in pedagogy is a material or mental imitation of what actually exists in the system by creating special analogs from which the principles of organization and operation of the system are produced. In order to achieve the goal of education, the meaningful foundations of the professional development model of the formation of the competitiveness of the leaders of the preschool educational organization should be rationally implemented.